Batman : ghosts - Kieth, Sam (DC Comics, 2018)
"Batman has always been Gotham's protector, watching over the city he has sworn to keep safe. But what happens when Batman has to face a foe he can't see? Find out in Batman: Ghosts, a classic graphic novel masterwork written and drawn by Sam Kieth (The Maxx, The Sandman). Homeless men and women are turning up dead all over Gotham City. The only clue the killer has left behind is a yellow powder: sulfur. Batman soon encounters the murderer and is shocked to find that it truly seems to be a monster--a shapeless creature, almost like...a ghost. Soon the man who stalks Gotham's streets by night finds himself being stalked. Batman is haunted by the ghost, who knows things about Bruce Wayne's past that no one (besides his trusted butler, Alfred) could possibly know. Who is this mysterious murderer, and what can Batman do to stop this intangible apparition with a penchant for killing?"--